Pendampingan Belajar Saat Pandemi Covid-19 Guna Meningkatkan Motivasi Belajar di SDN Makamhaji 03 - Andrian Iswanto (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The spread of Covid-19 in Indonesia affects various sectors of life, including education. Teaching and learning activities at elementary, junior high, high school and university levels are carried out with online learning. Learning assistance during the covid-19 pandemic is one of the efforts to implement the tri dharma of higher education in community service. This is done to increase student motivation and interest in learning activities. Learning assistance is located at SDN Makamhaji 03 Surakarta. The learning assistance method used is by providing direct learning assistance, namely students and students conducting the teaching and learning process face-to-face and directly. The target to be achieved in this community service is to increase the interest and motivation of students of SDN Makamhaji 03 during the covid-19 pandemic and increase learning time due to the implementation of alternating learning schemes per class. As a result, students become enthusiastic and motivated to continue learning and make good use of time during the covid-19 pandemic.